ANALISIS PENGGUNAAN METODE ISLAMIC MONTESSORI DALAM MENANAMKAN NILAI ISLAM PADA ANAK DI RA TUNAS LITERASI - Reki Tri Andriani; Asep Wijaya; Suriyanti (LPPM IAI Almuslim Aceh, 2023)
This research aims to determine the use of the Islamic Montessori method in instilling Islamic values ​​in children at RA Tunas Literasi. This research uses objects consisting of 7 teachers, with 5 questions. The research design of this study is qualitative research which uses observation checklists, interviews, and recording as instruments for collecting data. This research data analysis used a qualitative method which consists of several steps, namely collecting, coding, organizing, and interpreting data. The findings show that based on the results of observations and interviews, the conclusion of the analysis of the use of the Islamic Montessori method in instilling Islamic values ​​in children is as follows: it is very important to instill Islamic values ​​from an early age in children as a foundation in living life, by using the Islamic Montessori method children are more It is easy to understand Islamic values ​​by using the principles of the Montessori method, namely, experiential learning process, prepared environment, and peace education. The advantages of the Islamic Montessori method: it makes children more creative, and independent, and makes learning fun. Disadvantages: costs will be higher, and classrooms will be inadequate